Protegrin 1 Enhances Innate Cellular Defense via the Insulin-Like Growth Factor 1 Receptor Pathway - Penney, Jenna; Li, Julang (Frontiers in Cellular and Infection Microbiology, 2018)
Antimicrobial peptides (AMPs) represent a promising area of research to help combat the ever-growing problem of antibiotic resistance. Protegrin-1 is an AMP from the cathelicidin family. It is produced naturally in pigs and its mature form (mPG) has potent bactericidal properties and a unique β-hairpin structure that separates it from most AMPs found in mice and humans. While the antibacterial properties of protegrin-1 are well established, the role it plays in immune modulation has yet to be investigated, and our current study sought to explore this alternate role and potential mechanism behind. We found that mPG stimulated intestinal cell migration, this is accompanied with altered expression of genes associated with cell migration, in addition to increased expression of pro-inflammatory cytokines and immune-related factors. Further study suggested that mPG activates insulin-like growth factor 1 receptor (IGF1R) and through this receptor it modulates immune activity as well as cell migration. Our study revealed a novel function of mPG, and its associated pathway, suggesting therapeutic potential of the antimicrobial peptide for infection and/or immune disorders, particularly ones affecting the gastrointestinal tract such as inflammatory bowel syndrome.